Comparing the Sensitivity and Specificity of Touch Preparation Cytology and Pathology in Diagnose of Breast Lesions - Esmaeil Sadeghi; Mohammad Jafari (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Breast cancer is the common cancer in women and the major cause of death due to malignancy in women aged 40-44 years old. The routine method for diagnosis of biopsy specimens is pathologic procedure. Expert pathologists could accurately diagnose malignant and benign diseases using cytology methods. The aim of this study was to investigate the sensitivity and specificity of touch preparation cytology compared with pathology in diagnosis of breast lesions. Materials and methods: In this descriptive cross-sectional study we evaluated patients that had breast operation in Hamadan Bouali Hospital, 2016-2017 by analyzing pathologic recorded reports. Results: Totally 121 patients were studied including 114 (94.2%) females and 7 (5.8%) males. The mean age of the patients was 40.7 years (15-74 years). Malignant and benign diseases were observed in 61 and 60 patients, respectively. Sensitivity and specificity of touch preparation cytology were 91.8% and 95%, respectively. Positive predictive value and negative predictive value were 94.91% and 91.93%, respectively. Conclusion: Touch preparation cytology is an accurate and valid method for detecting benign breast lesions and is suggested to be used alongside frozen section to increase sensitivity and specificity of diagnosis.